Long‐term microtensile bond strength of self‐etch adhesives and influence of 7‐s phosphoric acid etching on adhesion of a 3‐step etch‐and‐rinse adhesive to the dentine of primary teeth. Issue 5 (9th March 2022) - Amend, Stefanie; Frankenberger, Roland; Oschmann, Tobias; Lücker, Susanne; Winter, Julia; Krämer, Norbert
Abstract: Background: The immediate microtensile bond strength (µTBS) of self‐etch (SE) adhesives to primary dentine is promising, but evidence about the durability is scarce. Aim: To assess the long‐term µTBS of SE adhesives to primary dentine and to examine the effect of 7‐s etching on µTBS of a 3‐step etch‐and‐rinse (ER) adhesive. Design: The enamel of 115 caries‐free human primary teeth was ground flat, and bonding was performed according to group assignment: G‐aenial™ Bond/GC [GB], Clearfil™ SE Bond/Kuraray [CS], OptiBond™ XTR/Kerr [OX], Scotchbond™ Universal/3M™ [SU], Prime&Bond ® NT™/Dentsply [PB], and OptiBond™ FL/Kerr [OF]. After storage (24 h, 6 mos., 12 mos.), 1, 762 beams were cut for µTBS testing. Fracture analysis was performed using light/fluorescence microscopy. Resin‐dentine interfaces were exemplarily analyzed using SEM. Results: After 24 h, OX and SU showed significantly higher estimated mean µTBS than GB, which exhibited the lowest µTBS at all stages ( p  < .05). μTBS within each adhesive group showed slight variations over time ( p  > .05). OF_SE produced acceptable µTBS. Etching increased the mean immediate µTBS for OF ( p  > .05) and the percentage of cohesive fractures. Conclusions: SE adhesives achieved durable μTBS to primary dentine. 7‐s etching may improve the immediate µTBS of a 3‐step ER adhesive.